DESAIN PENGUATAN PELAKSANAAN FUNGSI LEGISLASI DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA MENUJU PEMBAHARUAN HUKUM NASIONAL - SRI KARYATI (Universitas Mahasaraswati K. Mataram, 2022)
This study aims to find out how the ideal model for strengthening the implementation of the legislative function of the DPR RI in the context of reforming national law. Using a normative research method with a statutory approach. The results of the study show that the implementation of the legislative function of the DPR RI after the amendment to the constitution cannot be carried out optimally because it is indicated by the lack of legislative products and the low quality of the laws produced by the DPR. Legislation achievements that are not achieved according to the target of legislation and the number of laws submitted for judicial review at the Constitutional Court are benchmarks for the implementation of the legislative function of the DPR RI. And it can be concluded that the design of strengthening the implementation of the legislative functions of the DPR RI can be done by repositioning the Legislative Body of the DPR RI as a law center, strengthening the Supporting system of the DPR RI, and making a blue print for strengthening the implementation of the legislative functions of the DPR RI.